Safety of Favipiravir for Treatment of COVID-19: Latest Systematic Review - Rizki Oktarini; Anna Rozaliyani; Ratika Rahmasari; Muhammad Alkaff; Rani Sauriasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Adverse event studies of favipiravir use in treating COVID-19 have been ongoing since it was established as a treatment option. A better understanding of the side effects of favipiravir from recent studies is important in developing and assessing the recognition of effective treatments for COVID-19. Method: This was a systematic review based on studies and case reports on favipiravir monotherapy in COVID-19. Access to the included studies was gained via PubMed, SCOPUS, Science Direct, SpringerLink, and MedRxiv. Results: Twelve studies consisting of eight studies and four case reports were reviewed. The most common side effects were diarrhea, elevated liver enzyme levels, and hyperuricemia. None of which were significantly different from the comparison. Currently, various adverse event were reported in case reports such as drug fever,acute generalized exanthematous pustulosis (AGEP), and transient increase in viral load. The side effects would mostly be subsided after the treatment was discontinued.Conclusion: The use of favipiravir to treat COVID-19 caused dose-related side effects such as diarrhea, changes in liver enzymes, and increased level of uric acid. There were no serious side effectscompared to other antiviral drugs. To improve the efficacy and safety of COVID-19 therapy, it is important to prepare an incidence report of antiviral adverse events in special populations such as children, pregnant women, and patients with organ dysfunction.